2019
DOI: 10.1249/jsr.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Running Dose and Risk of Developing Lower-Extremity Osteoarthritis

Abstract: Whether or not running leads to the development of knee and hip osteoarthritis has been a much-debated topic and is often a question patients pose to their physicians. Recent literature adds to a growing body of evidence suggesting that lower-dose running may be protective against the development of osteoarthritis, whereas higher-dose running may increase one's risk of developing lower-extremity osteoarthritis. However, running dose remains challenging to define, leading to difficulty in providing firm recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 76 publications
1
22
0
1
Order By: Relevance
“…In the present study, we found that low-to-medium running led to unchanged or decreased brosis, vascularity, and surface cellularity in the IFP, which likely contributed to maintenance of optimal joint homeostasis. High-intensity running, however, may cause cartilage degradation [7]. This effect of high-intensity running may be, at least partially, attributable to the considerable increase in IFP brosis and vascularization as was found in the present study.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In the present study, we found that low-to-medium running led to unchanged or decreased brosis, vascularity, and surface cellularity in the IFP, which likely contributed to maintenance of optimal joint homeostasis. High-intensity running, however, may cause cartilage degradation [7]. This effect of high-intensity running may be, at least partially, attributable to the considerable increase in IFP brosis and vascularization as was found in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…Although accumulating evidence indicates that the IFP contributes to KOA by IFP contributes to KOA by modulating the phenotype of pro-or anti-in ammatory [3], its biological response to mechanical loading in the healthy knee is poorly understood. Mechanical factors have long been implicated in the etiology of OA [7]. An increased load on the knee may result in a signi cantly higher pressure inside the IFP at the extremes of extension and knee exion [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although accumulating evidence indicates that the IFP contributes to KOA by modulating the pro- or anti-inflammatory phenotype [ 3 ], its biological response to mechanical loading in the healthy knee is poorly understood. Mechanical factors have long been implicated in the etiology of OA [ 7 ]. An increased load on the knee may result in a significantly higher pressure inside the IFP at the extremes of extension and knee flexion [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, its effects on joint health appear to differ depending on the intensit y[ 10 ].. High-intensity running may induce a high degree of running-induced loading, which can be harmful to the joint once the magnitude exceeds the physiological tolerance level for an individual [ 7 , 10 , 11 ]. Currently, OA is regarded as a whole joint disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%